THE INFLUENCE OF SERVICE QUALITY AND PRICES ON CONSUMER LOYALTY THROUGH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE FOR TIKTOK SHOP USERS AT DIAN NUSWANTORO UNIVERSITY SEMARANG FEB - Marsela, Neni; Safitri, Maria; Mahmud, Mahmud; Nur Chasanah, Amalia (JURNAL EKBIS, 2024)
This research aims to analyze the influence of service quality and price on consumer loyalty through customer satisfaction as an intervening variable for TikTok shop users, either partially or simultaneously. This research is quantitative in nature and involves the population at Dian Nuswantoro University class of 2020 aged 21-25 years, who are users and make purchases at the TikTok shop. The sampling method used a probability sampling technique via a simple random sampling method, with a total of 172 respondents. The data collection technique uses primary data in the form of a questionnaire. The data analysis technique uses PLS-SEM version 4 software. This research obtained the results that service quality and price have a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on consumer loyalty, service quality has a positive and significant effect on consumer loyalty, price has an effect positive towards consumer loyalty.